1987
DOI: 10.1128/aem.53.9.2090-2097.1987
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lime and Phosphate on Nodulation of Soil-Grown Trifolium subterraneum L. by Indigenous Rhizobium trifolii

Abstract: Previous research had identified four serogroups of Rhizobium trifolii indigenous to the acidic Abiqua soil (fine, mixed, mesic Cumulic Ultic Haploxeroll). Nodulation of subterranean clover ( Trifolium subterraneum L.) by two of the serogroups, 6 and 36, was differentially influenced by an application of CaCO 3 which raised the pH of the soil from 5.0 to 6.5. These studies were designed to characterize this phenomenon more comprehensively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Site A is an improved subclover (T. subterraneum L.)-orchard grass (Dactylis glomerata L.) pasture located on a northwest-facing toe slope of Soap Creek Valley, approximately five miles north of Corvallis, Ore. Vicia species do not occur on the site because of heavy grazing by cattle. The soil is a silty-clay loam of the Abiqua series (fine, mixed, mesic, Cumulic Ultic Haploxeroll), and the site and soil characteristics have been described in detail elsewhere (1,3). Site C is an unimproved, ungrazed, open woodland area located mid-slope on the southeast-facing side of Soap Creek Valley.…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…Site A is an improved subclover (T. subterraneum L.)-orchard grass (Dactylis glomerata L.) pasture located on a northwest-facing toe slope of Soap Creek Valley, approximately five miles north of Corvallis, Ore. Vicia species do not occur on the site because of heavy grazing by cattle. The soil is a silty-clay loam of the Abiqua series (fine, mixed, mesic, Cumulic Ultic Haploxeroll), and the site and soil characteristics have been described in detail elsewhere (1,3). Site C is an unimproved, ungrazed, open woodland area located mid-slope on the southeast-facing side of Soap Creek Valley.…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…Soil samples were collected from a depth of 0 to 5 cm from a silty clay loam of the Abiqua series (Cumulic Ultic Haploxeroll) under permanent pasture. The physical and chemical characteristics of the soil have been described elsewhere (1,7). By using a soil tube auger, 20 soil cores were removed from within each of six grids (1 by 1 m) spaced 20 m apart along a transect running diagonally across the pasture.…”
Section: Methodsmentioning
confidence: 99%
“…Although immunofluorescence has allowed researchers to determine the densities of individual serotypes within indigenous soil populations of Bradyrhizobium japonicum (31,(36)(37)(38) and Rhizobium leguminosarum bv. trifolii (1,7,45), concern has been expressed about the proportion of cells which are viable within populations of soil rhizobia observed by immunofluorescence (3, 14,16,22,35). Even though there is evidence that nonviable rhizobia cannot persist for significant lengths of time in soil (5, 10), it is a longestablished fact that only a small fraction of the total bacterial population in soil enumerated by microscopy can be cultured (13,28,29,34,40,42).…”
mentioning
confidence: 99%
“…Application of KH 2 PO 4 (25 mg of P per kg of soil) to acidic soils significantly increased the percent nodule occupancy of Trifolium subterranean by R. leguminosarum bv. trifolii (17). The nodulation and N 2 fixation (nitrogenase activity) of T. vesiculosum increased significantly after the addition of P (100 mg per kg of soil) and K (300 mg per kg of soil); nitrogenase activity was doubled when the P concentration increased to 400 mg per kg of soil (194).…”
Section: Nutrient Deficiency Stressmentioning
confidence: 99%
“…Amelioration of subsoil acidity was also done by applying coal-derived calcium fulvate (324), and this treatment increased the pH more than did amelioration by gypsum, Ca-EDTA, Ca (OH) 2 , or CaCO 3 . Previous reports also indicate the importance of liming for improvement of growth and nodulation of legumes in acidic soils, since they indicated that liming raised the pH from 5 to 6.5 and increased the percentage of nodule occupancy of T. subterraneum (17). However, amelioration by lime and other substances, e.g., carbonate, must be optimized to avoid increasing the pH to a level which would be inhibitory to growth and symbiotic performance of legumes.…”
Section: Soil Acidity and Alkalinitymentioning
confidence: 99%